Septic shock due to Pseudomonas fulva potentially caused by percutaneous infection: A case report - Hiroki Kohno; Takuji Omoto; Tomohiro Taniguchi (IDCases, 2023)
Pseudomonas fulva is a Gram-negative rod that was isolated from Japanese paddy rice, and few cases of infections due to trauma, catheters, or contaminated infusion products have been reported. We report a case of P. fulva infection in an older patient who developed septic shock due to P. fulva during hospitalization after treatment for aspiration pneumonia. Since signs of infection were seen at the skin epidermal exfoliation site, which had been present since admission, this was considered to be the route of infection. The patient recovered on treatment with piperacillin. It was suggested that P. fulva can infect minor wounds in older individuals and lead to sepsis, even if the infection is not caused by a medical device or from severe trauma from an accident. This means that even small wounds, especially in older individuals, should be treated with caution, and a full body examination, including the skin, is essential even at the onset of sepsis. Although P. fulva has been identified as P. putida in many cases by conventional bacterial identification tests, it is expected that more cases will be accurately identified with the widespread use of polymerase chain reaction and mass spectrometry.